2021
DOI: 10.3390/batteries7040069
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Amorphous Carbon Coated LiNi0.6Mn0.2Co0.2O2 Cathode Material with Improved Capacity Retention for Lithium-Ion Batteries

Abstract: Coating conducting polymers onto active cathode materials has been proven to mitigate issues at high current densities stemming from the limited conducting abilities of the metal-oxides. In the present study, a carbon coating was applied onto nickel-rich NMC622 via polymerisation of furfuryl alcohol, followed by calcination, for the first time. The formation of a uniform amorphous carbon layer was observed with scanning- and transmission-electron microscopy (SEM and TEM) and X-ray photoelectron spectroscopy (X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…187 Considering that it is very challenging to establish a uniform carbon coating on the surface of NMC622 directly, it becomes interesting to achieve homogeneous surface coverage indirectly by the interaction of amorphous carbon-based materials in order to enhance the electrochemical properties. Kathribail et al 188 used the condensation reaction of furfuryl alcohol to form a poly-furfuryl coating on the surface of NMC622, which reduced the risk of oxidation of the carbon layer at high temperatures within air atmosphere. The homogeneous carbon-coated NMC622 with about 15 nm thickness obtained by roasting at 400 1C exhibited excellent electrochemical properties (Fig.…”
Section: Electrochemically Active Materials Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…187 Considering that it is very challenging to establish a uniform carbon coating on the surface of NMC622 directly, it becomes interesting to achieve homogeneous surface coverage indirectly by the interaction of amorphous carbon-based materials in order to enhance the electrochemical properties. Kathribail et al 188 used the condensation reaction of furfuryl alcohol to form a poly-furfuryl coating on the surface of NMC622, which reduced the risk of oxidation of the carbon layer at high temperatures within air atmosphere. The homogeneous carbon-coated NMC622 with about 15 nm thickness obtained by roasting at 400 1C exhibited excellent electrochemical properties (Fig.…”
Section: Electrochemically Active Materials Coatingmentioning
confidence: 99%
“…Kathribail et al . 188 used the condensation reaction of furfuryl alcohol to form a poly-furfuryl coating on the surface of NMC622, which reduced the risk of oxidation of the carbon layer at high temperatures within air atmosphere. The homogeneous carbon-coated NMC622 with about 15 nm thickness obtained by roasting at 400 °C exhibited excellent electrochemical properties (Fig.…”
Section: Investigation On Strategies To Suppress the Degradation Of T...mentioning
confidence: 99%
“…Surface coating can improve the stability of the surface structure of the material, promote the transfer of electrons on the surface of the material, and prolong the service life of the material. At present, commonly used coating materials include carbon materials (amorphous carbon [48][49][50], graphene [51][52][53], carbon nanotubes [54,55]), phosphate (Li3PO4 [56][57][58], LiFePO4 [59], MnPO4 [60]), fluoride (CaF2 [61], AlF3 [62], LiF [63]), oxides (LiBO3 [64], LiWO3 [65], Li2TiO3 [66], WO3 [67], SiO2 [68], Al2O3 [69], CeO2 [70]) etc.…”
Section: Surface Coatingmentioning
confidence: 99%
“…Although conductive carbon coating on the CAM surface is frequently used in conventional LIBs to improve the electronic conductivity of the cathode, 30,31 this approach is not suitable for ASSBs using sulfide SEs because the coated carbon must contact the SEs, which would lead to detrimental decomposition reactions (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
“…18 Park et al demonstrated that the use of graphitized carbon with fewer functional groups in the composite cathode improved the reversible capacity and cycling stability. 29 Although conductive carbon coating on the CAM surface is frequently used in conventional LIBs to improve the electronic conductivity of the cathode, 30,31 this approach is not suitable for ASSBs using sulde SEs because the coated carbon must contact the SEs, which would lead to detrimental decomposition reactions (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%